Rationale for and Design of the Study of Early Enteral Dextrose in Sepsis: A Pilot Placebo‐Controlled Randomized Clinical Trial. Issue 3 (30th May 2019) - Shah, Faraaz Ali; Kitsios, Georgios D.; Zhang, Yingze; Morris, Alison; Yende, Sachin; Huang, David T.; O'Donnell, Christopher P.; McVerry, Bryan J.
Abstract: Background: Sepsis is characterized by life‐threatening organ dysfunction caused by a dysregulated host response to infection and affects over 1 million Americans annually. Loss of glycemic control in sepsis is associated with increased morbidity and mortality, and novel approaches are needed to promote euglycemia and improve outcomes in sepsis. Recent studies from our laboratory demonstrate that early low‐level enteral dextrose infusion in septic mice attenuates the systemic inflammatory response and improves glycemic control by inducing intestine‐derived incretin hormone secretion. Aim: The aim of the Study of Early Enteral Dextrose in Sepsis (SEEDS) is to test the effect of a 24‐hour enteral dextrose infusion in critically ill septic patients as a therapeutic agent to decrease systemic inflammation and promote euglycemia. Methods: SEEDS is a single‐center, double‐blind, randomized, controlled trial that will enroll 60 septic patients admitted to the intensive care units at the University of Pittsburgh Medical Center Health System in Pittsburgh. Participants will be randomized 1:1 to receive enteral dextrose (n = 30) or water (placebo, n = 30) infusion for 24 hours. The primary outcome is the circulating interleukin‐6 level measured after the 24‐hour infusion compared between dextrose and placebo groups. Secondary outcomes include postinfusion circulating insulin, incretin, and other proinflammatory cytokine levels, as well as incidence of hyperglycemia and hypoglycemia during the infusion period. Discussion: This trial will characterize the effects of early enteral dextrose on endogenous endocrine pathways and the systemic inflammatory response in sepsis. The results of this trial will inform future larger interventional studies of early enteral nutrients in critically ill patients with sepsis.